2009
DOI: 10.1093/annonc/mdp002
|View full text |Cite
|
Sign up to set email alerts
|

Class III β-tubulin, but not ERCC1, is a strong predictive and prognostic marker in locally advanced head and neck squamous cell carcinoma

Abstract: TUBB3 is a predictive and prognostic marker along with well-known p53 in HNSCC patients receiving cisplatin-based induction chemotherapy. Clinical impact of ERCC1 is not evident in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 24 publications
2
53
3
Order By: Relevance
“…Therefore, prediction of the anticancer effects of cisplatin-based chemotherapy is important in planning treatment strategies. In several malignancies, increased expression of TUBB3 was reported to be significantly associated with poor prognosis and survival in patients receiving platinum-based chemotherapy (24,25). Therefore, we expected that TUBB3 expression would be significantly associated with the anticancer effect of cisplatin-based chemotherapy in patients with advanced UC; however, our results did not support this hypothesis.…”
Section: Discussioncontrasting
confidence: 79%
“…Therefore, prediction of the anticancer effects of cisplatin-based chemotherapy is important in planning treatment strategies. In several malignancies, increased expression of TUBB3 was reported to be significantly associated with poor prognosis and survival in patients receiving platinum-based chemotherapy (24,25). Therefore, we expected that TUBB3 expression would be significantly associated with the anticancer effect of cisplatin-based chemotherapy in patients with advanced UC; however, our results did not support this hypothesis.…”
Section: Discussioncontrasting
confidence: 79%
“…A similar deleterious effect for high ERCC1 expression was shown in 45 HNSCC patients treated with cisplatin-based chemoradiation (25), and also among 34 HNSCC treated by induction chemotherapy (cisplatin and docetaxel) followed by concurrent cisplatinbased chemoradiation (26). More recently, two other studies have shown no influence on response rate or survival for ERCC1 expression in HNSSC patients treated by cisplatinbased induction chemotherapy, followed by radiation therapy or radical surgery, or concurrent cisplatin, radiotherapy and cetuximab (27,28). On the other hand, studies done in two other tobacco-related cancers, namely non-small cell lung cancer and pancreatic adenocarcinoma, treated by surgery alone, indicate that ERCC1 positivity may implicate in a favorable prognosis, which is in line with our results (13,14,29).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, we found classes II and III b-tubulin Endocrine-Related Cancer (2011) 18 85-95 www.endocrinology-journals.org expression to be mutually exclusive, suggesting a complex regulatory mechanism. In other tumor types, isotype III has been detected in 36% of gastric (Urano et al 2006), 40% of head and neck (Koh et al 2009), and 84% of breast (Paradiso et al 2005) cancer samples respectively. b-tubulin III tumoral overexpression has been associated with poor prognosis in a variety of cancer types (Seve et al 2005, Seve & Dumontet 2008, Koh et al 2009, including ovarian carcinomas (Ferrandina et al 2006), although there is one contradictory report (Aoki et al 2009) in clear cell ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian carcinoma, high protein levels of classes I and IV, intermediate levels of class III, and low levels of class II b-tubulin have been reported (Ohishi et al 2007). High tumoral b-tubulin III expression has been associated with worse survival in non-small cell lung cancer (Rosell et al 2003, Seve et al 2005, breast (Seve & Dumontet 2008), head and neck (Koh et al 2009), and ovarian cancer (Ferrandina et al 2006), although Aoki et al (2009) reported a better survival for patients with ovarian clear cell adenocarcinoma positive for class III expression. In ovarian cancer, b-tubulin III has also been associated with worse treatment response (Kavallaris et al 1997, Mozzetti et al 2005, Umezu et al 2008.…”
Section: Introductionmentioning
confidence: 99%